2010
DOI: 10.1111/j.1600-0765.2010.01309.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-binding protein-2 and -3 in gingival crevicular fluid

Abstract: These results indicate that IGFBP-2 is a potential novel marker for periodontal disease progression. As IGFBP-2 modulates bone metabolism and cell migration, IGFBP-2 in the gingival crevicular fluid may reflect periodontal disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
2
3
1
Order By: Relevance
“…However, in this study, the correlation between the clinical parameters assessed using OHIs, BOP, PPD, CAL, and CPI with biochemical parameters did not demonstrate any significant association. These findings were contradictory to the findings reported by Takenouchi et al, where they found a positive correlation between the concentration of IGFBP-2 and the probing depth and gingival index but not for IGFBP-3 [ 30 ]. It has been shown that IGFBP-3 regulates epidermal homeostasis by localizing to the nucleus of numerous cultivated cell lines, including epidermal keratinocytes, perhaps by influencing the early stages of keratinocyte terminal differentiation.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in this study, the correlation between the clinical parameters assessed using OHIs, BOP, PPD, CAL, and CPI with biochemical parameters did not demonstrate any significant association. These findings were contradictory to the findings reported by Takenouchi et al, where they found a positive correlation between the concentration of IGFBP-2 and the probing depth and gingival index but not for IGFBP-3 [ 30 ]. It has been shown that IGFBP-3 regulates epidermal homeostasis by localizing to the nucleus of numerous cultivated cell lines, including epidermal keratinocytes, perhaps by influencing the early stages of keratinocyte terminal differentiation.…”
Section: Discussioncontrasting
confidence: 99%
“…IGFBP-3 has several roles both in systemic and in local regulation (Yamada & Lee 2009), and is a local stimulator of IGF action in bone (Govoni et al 2005). Takenouchi et al found a weak, but non-significant, inverse association between IG-FBP-3 in the gingival crevicular fluid (GCF) and probing depth (Takenouchi et al 2010). Their results are in line with our findings, despite the divergence regarding the selected clinical parameters of periodontal disease.…”
Section: Igfbp-3supporting
confidence: 92%
“…However, the protective effect of serum IGFBP-3 levels on mean CAL was restricted to levels between 300 and 1200 ng/ml (Fig. Takenouchi et al found a weak, but non-significant, inverse association between IG-FBP-3 in the gingival crevicular fluid (GCF) and probing depth (Takenouchi et al 2010). Results support the assumption that serum IGFBP-3 levels might be associated with local homeostasis in periodontal tissue.…”
Section: Igfbp-3mentioning
confidence: 83%
“…The upregulation of IGFBP-3 in human gingival fibroblasts increased IGF transport and enhanced periodontal wound healing and regeneration [58]. There was no 17 Disease Markers correlation between IGFBP-3 levels in gingival crevicular fluid with periodontal parameters (e.g., probing depth and gingival index) [59].…”
Section: Discussionmentioning
confidence: 99%